Effect of Cement Type, Relining Procedure, and Length of Cementation on Pull-out Bond Strength of Fiber Posts - Macedo, Vanessa Cruz [UNESP]; Faria e Silva, Andre Luis; Marcondes Martins, Luis Roberto (Elsevier B.V., 2010)
Introduction: As opposed to the cementation metal posts, the cementation of fiber posts has several details that can significantly influence the success of post retention. This study evaluated the effect of the relining procedure, the cement type, and the luted length of the post on fiber posts retention. Methods: One hundred eighty bovine incisors were selected to assess post retention; after endodontic treatment, the canals were flared with diamonds burs. Post holes were prepared in lengths of 5, 7.5, and 10 mm; the fiber posts were relined with composite resin and luted with RelyX ARC, RelyX Unicem, or RelyX Luting 2. All cements are manufactured by 3M ESPE (St. Paul, MN). Samples were subjected to a pull-out bond strength test in a universal testing machine; the results (N) were submitted to a three-way analysis of variance and the Tukey post hoc test (alpha = 0.05). Results: The improvement of post retention occurred with the increase of the post length luted into the root canal; the relining procedure improved the pull-out bond strength. RelyX Unicem and RelyX ARC showed similar values of retention, both showing higher values than RelyX Luting 2. Conclusion: Post length, the reining procedure, and the cement type are all important factors for improving the retention of fiber posts. (J Endod 2010;36:1543-1546)
Keywords: Bond strength; fiber post; resin cement